A View from a Within: Formasi Identitas Kolektif ASEAN dalam Proses Perumusan ASEAN Outlook on the Indo-Pacific - Hafizon, Muhammad Iqbal; Ramadhan, Rizki Ananda (Padjadjaran Journal of International Relations, 2024)
Artikel ini membahas evolusi konsep Indo-Pasifik sebagai kerangka kerja arsitektur regional. Dengan momen penting pada tahun 2018, Amerika Serikat memperkenalkan Strategi Indo-Pasifik Bebas dan Terbuka, merespons ketegangan geopolitik yang meningkat dan bertujuan untuk melawan pengaruh Tiongkok. Di tengah-tengah lanskap ini, semua negara anggota ASEAN secara resmi mengadopsi Pandangan ASEAN tentang Indo-Pasifik (AOIP) selama KTT ASEAN ke-34 pada tahun 2019. Dengan menggunakan Formasi Identitas Kolektif dari Alexander Wendt, penelitian ini melakukan analisis wacana kualitatif untuk melihat proses pembentukan wacana ASEAN tentang Indo-Pasifik. Dengan menggunakan analisis diskursus, riset ini mengungkap interaksi yang rumit di antara negara-negara ASEAN dalam membentuk wacana arsitektur regional. This article delves into the evolution of the Indo-Pacific concept as a regional architectural framework. In a pivotal moment in 2018, the United States introduced the Free and Open Indo-Pacific Strategy, responding to growing geopolitical tensions and aiming to counter China's influence. Amidst this landscape, all ASEAN member states officially embraced the ASEAN Outlook on the Indo-Pacific (AOIP) during the 34th ASEAN Summit in 2019. Employing Alexander Wendt's Collective Identity Formation framework, this research conducts a qualitative discourse analysis to scrutinize the process of ASEAN's discourse formation on the Indo-Pacific. Utilizing various data collection methods, including interviews and document analysis, the study unveils intricate interactions among ASEAN states in shaping the regional architecture discourse.